(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the status of skipping breakfast among Preventive Medicine students of Thai Nguyen University of Medicine and Pharmacy in 2025 and some factors related . Research subjects and methods: Students are studying Preventive Medicine at the Thai Nguyen University of Medicine and Pharmacy. A cross-sectional descriptive study. Results: The percentage of students skipping breakfast was 64.6%. The group eating breakfast 1-2 days/week accounted for the largest percentage (28.2%), while only 19.5% maintained a full breakfast every day. The percentage spending less than 10 minutes on breakfast was quite high (26%), and 13% did not care about breakfast time, with only 8.3% spending more than 20 minutes. A small percentage (3.3%) still considered breakfast unnecessary. Conclusion: Conclusion: Medical students in general, and Preventive Medicine students in particular, are an important group in society, but frequently skipping breakfast leads to extremely serious health consequences. Maintaining a diet with three meals a day, especially breakfast, is extremely important for improving nutrition.